Effects of crisis and political change, 1997-1999 - Sunderlin, William D. (Resources for the Future, Center for International Forestry Research (CIFOR) and Institute of Southeast Asian Studies (ISEAS), 2002)
An economic crisis and political changes that have occurred in Indonesia since 1997 have presented grave dangers but also important opportunities for the country. On the one hand, the depreciation of the rupiah against the dollar is part of a drastic economic downturn, but on the other hand, it represents an opportunity for increased competitiveness of Indonesian exports and for increased prosperity for those involved in the export economy. The changeover of regimes from Soeharto to B.J. Habibie led to much political instability, which compounded economic problems, but at the same time it has offered the potential for fundamental policy changes. This article assesses the consequences of these changes -- both negative and positive -- on people living in forested areas, on commercial activity within the forest sector and on the extent of forest itself. Among the findings are that: (1) two-thirds of the people in forested areas have become worse off during the crisis compared with their situation in the year before the crisis; (2) during the crisis small farmers increased clearing of forests for perennial tree crops and decreased attention to food crops in shifting cultivation systems; (3) pulp and paper have replaced plywood as the mainstay source of export revenue in the forest sector, although the origins of this transformation pre-date the crisis and the change cannot be solely explained by the crisis; (4) illegal logging has boomed during the crisis, but also cannot be entirely explained by the crisis; (5) oil palm development has slowed in the crisis period but is poised for future growth; and (6) positive forest policy changes have been introduced but in general fall short of the expectations of the reform community in Indonesia.